Homes Incorporated: Offshore Ownership of Real Estate in the U.K. - Niels Johannesen; Jakob Miethe; Daniel Weishaar (Center for Economic Studies and ifo Institute (CESifo), 2022)
Ownership of real estate through corporations in offshore tax havens creates opportunities for tax evasion and money laundering and may have undesirable effects in housing markets. In this paper, we study offshore ownership of real estate in the United Kingdom by combining several data sources: administrative data from the land register, a comprehensive transaction database, a propriety database on corporate ownership links, and a handful of offshore data leaks. Our descriptive analysis shows that the market share of offshore corporations has increased over time and varies strongly across market segments: It currently stands at 1.25% in the overall residential market and around 15% for top-end properties. When data leaks allow us to trace ownership through offshore corporations to the beneficial owners, we find that around half have ties to Africa, Asia and the Middle East, but that the largest 'foreign' investor is the United Kingdom itself. Turning to causal evidence, we show that changes in tax incentives and ownership transparency induce strong responses in patterns of offshore ownership, suggesting that both taxation and secrecy are important motives for the beneficial owners. Finally, we show that the Brexit referendum was followed by a sharp increase in property sales by offshore owners and a large differential decrease in property prices in local areas with more offshore ownership, conditional on area and property characteristics. This suggests that the reduction in demand from offshore investors triggered by Brexit had a negative causal effect on property prices and, more broadly, that offshore ownership can have significant real effects in housing markets.
Keywords: H26; F21; R31; 330; tax havens; tax evasion; offshore financial centers; real estate; hidden wealth